Penginjilan Kepada Kaum Apatis : Menerapkan Prinsip Fleksibilitas dari 1 Korintus 9:19-27 - Yeremia Hia; Rendi Risky Laowo; Setulus Hati Laia (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
This study explores the challenges of evangelism in the modern era, particularly in reaching groups that are apathetic towards the gospel. Using 1 Corinthians 9:19-27 as its foundation, which highlights the importance of flexibility in evangelistic approaches to reach people from various backgrounds, this research applies the Apostle Paul’s concept of adaptability to contemporary evangelism among apathetic groups. Specifically, it examines how biblically-based adaptive strategies can be utilized by churches and individual Christians in their evangelistic mission. The primary aim of this study is to analyze the application of the principle of flexibility in 1 Corinthians 9:19-27 for apathetic groups and to assess how this principle can enhance the effectiveness of evangelism in today’s context. Through this research, it is hoped that new, more relevant approaches for ministry in a diverse society will be identified. This study employs a qualitative method, using biblical text analysis and systematic theological reflection. Findings indicate that applying the principle of flexibility in evangelism is not only effective in addressing apathy, but also allows evangelists to build more personal and empathetic relationships with those they seek to reach. In Paul’s sense, flexibility involves adapting without compromising gospel truth, offering a pertinent strategy for meeting the challenges of evangelizing to apathetic individuals.